Analisis Bagi Hasil Pembiayaan Mudlarabah Di Bank Syariah Mandiri Cabang Pembantu Lumajang - Indra Hidayatullah (JES (Jurnal Ekonomi Syariah), 2018)
Profit and loss sharing system applied in the Islamic bank as an alternative substitute for the application of the interest system is deemed to successfully avoid the negative impacts of the interest application. It is also considered to be able to allocate resources and fund sources efficiently. The solution is briefly mentioned by holding the financing transactions based on three models, namely mudlarabah, musharakah dan murabahah. In this study, there are several methods used to collect the data. It includes methods of observation, interviews and documentation. The data is then analyzed using descriptive analysis and qualitative approach. The research findings figure out that the realization of profit and loss sharing system based on mudlarabah financing applied in the Branch Office of Syariah Mandiri Bank in Lumajang, in terms of Islamic Law, is valid since it already fulfills the validity requisites of mudlarabah. There is only such dilemmatic consideration relates to the issue of assurance because of the difference opinion among Islamic scholars (Ulama) about the license of assurance itself aside of the emergency or in case that the suspicion toward mudlarib emerged. The financing of mudlarabah in Syariah Banking, particularly in terms of the application of financing calculation in the Branch Office of Syariah Mandiri Bank in Lumajang is completely appropriate since it already fulfills the requisites obtained in all Syariah Bankings and the Fatwa of National Syariah Council. The application of profit and loss sharing calculation in the Branch Office of Syariah Mandiri Bank in Lumajang is valid and appropriate since its realization is in accordance with Islamic and Banking Law. The profit-sharing ratio provided by the bank are 95.10%: 4.9%, 90, 69%: 9.31% and 87.10%: 12.9%. And this bank do not share the ratio of 100: 0 to their customers. Keywords: Profit and Loss Sharing, Mudlarabah financing, Islamic Perspective